2009
DOI: 10.1088/1126-6708/2009/12/030
|View full text |Cite
|
Sign up to set email alerts
|

Waiting for μ →eγ from the MEG experiment

Abstract: The Standard Model (SM) predictions for the lepton flavor-violating (LFV) processes like µ → eγ are well far from any realistic experimental resolution, thus, the appearance of µ → eγ at the running MEG experiment would unambiguously point towards a New Physics (NP) signal. In this article, we discuss the phenomenological implications in case of observation/improved upper bound on µ → eγ at the running MEG experiment for supersymmetric (SUSY) scenarios with a see-saw mechanism accounting for the neutrino masse… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 100 publications
2
19
0
Order By: Relevance
“…A large mixing angle leads to similar contributions to both LFV decays which renders the τ channel non-competitive. Similar results are found in [35], where also a study using SU(5) without right-handed neutrinos is performed exhibiting larger differences between the τ → γ and µ → eγ branching fractions, although the predicted effects are smaller in general than for supersymmetric GUT seesaw models.…”
Section: Lepton Flavour Violation In τ Decayssupporting
confidence: 84%
“…A large mixing angle leads to similar contributions to both LFV decays which renders the τ channel non-competitive. Similar results are found in [35], where also a study using SU(5) without right-handed neutrinos is performed exhibiting larger differences between the τ → γ and µ → eγ branching fractions, although the predicted effects are smaller in general than for supersymmetric GUT seesaw models.…”
Section: Lepton Flavour Violation In τ Decayssupporting
confidence: 84%
“…Selected reviews of these topics can be found in [7,23,[344][345][346], where many references can be found. The study of correlations between LFV, (g − 2) µ and EDMs in supersymmetric flavour models and SUSY GUTS can be found in [35,[347][348][349]. Analogous correlations in models with vector-like leptons have been presented in [350] and general expressions for these observables in terms of Wilson coefficients of dimension-six operators can be found in [351].…”
Section: Preliminariesmentioning
confidence: 92%
“…being the average sfermion mass); in SUSY seesaw models the main contributions are approximately given by the following expression [15]:…”
Section: B Susy Seesawmentioning
confidence: 99%